Field notes contributed by J. Donald Gillaspey, Lamoni, Iowa, winter 1983-1984 - Gillaspey, J. Donaldet al (1983)
Field notes were contributed by J. Donald Gillaspey, Lamoni, Iowa, winter 1983-1984. He reported all species of hawks were extremely scarce that winter. Richard Erke sighted a Goshawk at Slip Bluff Park, and Jeff and Clark Livingston sighted a Hooded Merganser on a farm pond. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed